Reduction in Door-to-Needle Time after Transfer of Thrombolysis Site from CCU to Emergency Department - Osama Mohammed; Firjith C. Paramba; Naushad V. Aboobaker; Riyadh A. Mohammed; Nishan K. Purayil; Haitham M. Jassim; Mohammad K. Shariff; Saud M. Aslam; Farook F. Muhsen; Khalid H. Al Noor; Hani H. Al Kilani (Emergency Medicine International)
Objective. Early restoration of coronary perfusion by thrombolysis or percutaneous coronary intervention is the main modality of treatment to salvage the ischemic myocardium. The earlier the procedure is completed, the greater the benefit is in saving myocardium and restoring its functions. The aim of the study is to compare the door-to-needle time (DNT) in acute ST elevation myocardial infarction (STEMI) in the period prior to December 2008 when the site of thrombolysis was in coronary care unit (CCU) and the period after that when the site was shifted to emergency department (ED). Methods. A retrospective, descriptive study was conducted at Al Khor Hospital, Qatar, in patients with acute STEMI who underwent thrombolysis at CCU and ED from April 2005 until December 2011, to compare the DNT, duration of hospitalization, and mortality. Results. A total of 211 patients with acute STEMI were eligible for thrombolysis; 58 patients were thrombolysed in the CCU and 153 in ED. The median DNT was reduced from 33.5 minutes in the CCU to 17 minutes in the ED representing a reduction of more than 50% with a P value of < 0.0001. Conclusion. The transfer of the thrombolysis site from CCU to the ED was associated with a dramatic and significant reduction in median door-to-needle time by more than half.